Professionalism, professionalization, expertise and compassion: a qualitative study of medical residents. Issue 1 (December 2017) - Phillips, Susan; Dalgarno, Nancy
Abstract Background Formal and informal medical curricula convey expectations about professionalization, that is, the development of physician identity, and also about professionalism. This study examined whether, in general, junior residents experienced any dissonance between these roles and focused particularly on how they negotiated conflicts between compassion, self-care, duty and medical expertise. Methods In 2015, purposive sampling was used to select 21 first-year residents at a Canadian medical school. Participants listened to a 5-min audio-recording narrated in either male or female voice. Facing compassion fatigue after three obstetrical disasters over less than 2 days the resident narrator asks to go home. Participants reacted in writing to questions about this request and relevant teaching/modelling. Responses were analyzed using a qualitative, exploratory, thematic research design. Results Four themes were identified: i) empathy, self-doubt and fear of weakness, ii) the need for support from and communication with physicians and others, iii) education received, and iv) professionalization outranks professionalism. Participants agreed that under the circumstances the narrator's care, compassion and request were appropriate. Never the less, many grappled with feeling that asking to be relieved of work demonstrated weakness and a shirking of responsibility. Respondents had received no formal teaching about balancing compassion for patients or self with professional duty. Preceptors' informal teaching and modeling valorized scientific disengagement above all else. What emerged was participants' drive to become detached clinicians who set aside emotional responses and interactions that could impede and be incompatible with professionalization. However, participants also recognized and lamented what was lost in such a transformation. Conclusion In the transition from student to practitioner, trainees' views and the modeling they receive shift emotion and compassion, whether for self or patients, from assets to liabilities as they aim to be invincible medical experts.